2013
DOI: 10.7343/as-016-013-0040
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of the groundwater flow in the fractured and karst aquifer of the Salento peninsula (Southern Italy)

Abstract: Water resources represented by coastal aquifers are very important for regions characterized by a relevant request of freshwater, but limited rainfall, lack of surface water bodies and intrusion of the seawater through the sediments which host groundwater. Therefore some coastal areas, like the Salento peninsula (southern Italy), are subjected to the risk of desertification and a proper management of groundwater resources requires tools to analyze and predict the water balance and the evolution of the physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
(25 reference statements)
1
12
0
Order By: Relevance
“…In particular, both the bands at 560 and 610 nm are typical for quartz and are intrinsic of the bulk structure [20]. The comparison between the chemical and mineralogical composition of our findings and a series of previous geological studies on the pits of Calabria [21][22][23][24] allows to conclude that the materials used in the Church construction were taken from a quarry found along the Tyrrhenian coast of Northern Calabria, rich in this natural stone [21] and located close to the Church.…”
Section: Resultssupporting
confidence: 57%
“…In particular, both the bands at 560 and 610 nm are typical for quartz and are intrinsic of the bulk structure [20]. The comparison between the chemical and mineralogical composition of our findings and a series of previous geological studies on the pits of Calabria [21][22][23][24] allows to conclude that the materials used in the Church construction were taken from a quarry found along the Tyrrhenian coast of Northern Calabria, rich in this natural stone [21] and located close to the Church.…”
Section: Resultssupporting
confidence: 57%
“…On the other hand, salinity would increase up to more than 5000 mg/l in 2060, especially along the western Ionian coast. Generally speaking, a full comparison between results obtained by Giudici et al [28] and De Filippis et al [32] and those obtained by Romanazzi et al [36] cannot be performed. As an example, the piezometric trend simulated by Romanazzi et al [36] is smoother, with a watershed which can be clearly identified in the center of the peninsula.…”
Section: Introductionmentioning
confidence: 91%
“…Anthropogenic stresses are further exacerbated by tourism activities during the summer season. In this framework, an alarming imbalance between freshwater demand and groundwater availability and a high vulnerability to saltwater intrusion have been detected in the last decades either by monitoring [29,30] and modelling [28,[31][32][33][34][35][36]. This represents a major concern in this coastal ecosystem, as salinization may cause negative impacts on irrigated crops, soil fertility [37], and the socioeconomic development of the region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monitoring and modelling studies of the aquifer balance in the last decades (Margiotta and Negri, 2005;Portoghese et al, 2005;Romanazzi and Polemio, 2013) showed a decreasing aquifer pressure with increasing salty seawater intrusion. Thus, efforts have been recently made to specifically modelling the groundwater flow in the fractured karst aquifer (Giudici et al, 2012;De Filippis et al, 2013). The aim of this work is to present a data set of long term experimental measurements of the surface energy and water balance as measured by the CNR-ISAC micrometeorological station in Salento peninsula (the only available long term data set in Salento, to the authors' knowledge), and to give an experimental support to the hydrological modelling for the local water resources management.…”
Section: Introductionmentioning
confidence: 99%